2021
DOI: 10.3390/sym13112219
|View full text |Cite
|
Sign up to set email alerts
|

Are We Right about the Right TPJ? A Review of Brain Stimulation and Social Cognition in the Right Temporal Parietal Junction

Abstract: In the past decade, the functional role of the TPJ (Temporal Parietal Junction) has become more evident in terms of its contribution to social cognition. Studies have revealed the TPJ as a ‘distinguisher’ of self and other with research focused on non-clinical populations as well as in individuals with Autism and Type I Schizophrenia. Further research has focused on the integration of self-other distinctions with proprioception. Much of what we now know about the causal role of the right TPJ derives from TMS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 124 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…That is not to say pride does not involve frontal regions [ 108 ]. However, we assume that as ToM requirements increase, there will be a bigger pull of rTPJ [ 109 ]. To test this, we examined excessive pride in a non-clinical sample [ 110 ].…”
Section: Pridementioning
confidence: 99%
“…That is not to say pride does not involve frontal regions [ 108 ]. However, we assume that as ToM requirements increase, there will be a bigger pull of rTPJ [ 109 ]. To test this, we examined excessive pride in a non-clinical sample [ 110 ].…”
Section: Pridementioning
confidence: 99%
“…Brain stimulation studies showed that disrupting the TPJ reduces people’s ability to mentalise with others or even with their own future self ( 22 ). Potentially, this is because the TPJ is required to differentiate one’s own thoughts and feelings from other people’s ( 23 ). Precuneus and medial PFC, on the other hand, might be important for attributing mental states to other people ( 21 ), and default mode network connectivity in the medial PFC correlates with social (dys)function ( 24 ).…”
Section: Mentalisingmentioning
confidence: 99%